Design and Development of a Simple 2.45 GHz Microwave Plasma-in-Liquid System: Characteristics in Deionized Water and NaCl Solution - Muh. Firdan Nurdin; Sudirman Sudirman; Yunas Yunas; Andi Erwin Eka Putra; Novriany Amaliyah (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2026)
Plasma, the fourth state of matter, holds significant potential for industrial applications including material processing, energy conversion, and liquid waste treatment. Among the effective methods for plasma generation is the use of 2.45 GHz microwave energy. This study designed and constructed a simple microwave-based plasma-in-liquid system and evaluated the plasma characteristics formed in two liquid media: deionized water and a 5% sodium chloride (NaCl) solution. The system comprised a modified household microwave oven, an aluminum WG9A-type waveguide, and an acrylic plasma reactor fitted with tungsten electrodes. Experiments were conducted at atmospheric pressure (1 atm) with 100 mL of liquid irradiated for 60 s (n = 5 per medium). Plasma did not form in deionized water under any trial, whereas the NaCl solution consistently produced plasma exhibiting an intense orange emission. The mean final temperature was higher in the NaCl solution (78.2 ± 12.2 °C) than in deionized water (60.6 ± 14.2 °C); however, a Welch's two-sample t-test indicated this difference did not reach statistical significance at the 0.05 level (t = 2.11, p = 0.069), a result attributable to the limited sample size and to the unequal initial temperatures recorded across trials. Despite the absence of statistical significance, the qualitative outcome was unambiguous and fully reproducible: plasma ignition occurred in all five NaCl trials and in none of the five deionized-water trials, confirming that electrical conductivity of the liquid medium rather than bulk temperature alone is the governing factor for atmospheric plasma-in-liquid ignition in this system. The developed apparatus provides a low-cost, replicable platform suitable for fundamental plasma research and engineering education.